Persepsi Masyarakat Terhadap Iklan Rokok di Negeri Passo, Kecamatan Baguala, Kota Ambon - Yani Talakua (SIMULACRA: JURNAL SOSIOLOGI, 2018)
Smoking is a bad habit that has been done since the time of the discovery of tobacco. Initially smoking only aims to warm the body but, over time the habit becomes changed goal is as a requirement that can not be abandoned or can be said to be addicted. Without tobacco as if there is no pleasure in itself. This continued until the time of the industrial revolution in England until the emergence of cigarette factories to spread throughout the world. The majority of smokers worldwide are ± 47% male population while 12% are female population with different age categories. Various reasons people smoke a variety, among these people there are several factors that influence a person to smoke for example, prestige factors to be called "champion", and there are also people who say smoking can trigger inspiration and keupayaan thinking, even there is an interesting pantun used as justification for the smoking habit that is "there is a rooster on the roof, not smoking not handsome" there is also a saying that "smoking dead do not smoke is also dead." Smoking is one problem that is difficult to solve. Moreover, it has become a national problem, and even international. This becomes difficult, because it is related to many factors that trigger each other, so as if it has become a vicious circle. Cigarettes are cylinders of paper length between 70 to 120 mm (varies by country) with a diameter of about 10 mm containing tobacco leaves that have been chopped. As for several types of cigarettes in Indonesia, among others: Djarum Super, Gudang Garam Filter, Gudang Garam Merah, Dji Sam Soe, Sampoerna Mild, Sampoerna Mild Menthol, Marlboro, Surya, U Mild and others. In terms of cigarette health can cause negative effects for active smokers and passive smokers, because each suction causing nicotine and carbon monoxide are very dangerous for both especially for active smokers who can cause various chronic diseases, such as lung cancer, bladder cancer, cervical cancer , breast cancer, esophageal cancer, digestion, kidney cancer, oral cancer, atherosclerosis, impotence and heart attacks, to death.